Madrasah Education Reform In Indonesia - Sudarto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Education in Islam is placed as something essential in human life. Through education, humans can shape their personality. In addition, through education humans can understand and be able to translate the environment they face so that they can create a brilliant work. Madrasas in building national character by instilling religious values as part of the implementation of education besides providing general knowledge need to be a concern. Because the implementation of madrasah education has encouraged education in Indonesia to be even greater. Until now, madrasas are still looking for their ideal form. The identification of madrasas boils down to two things, namely the problem of interly (tug-grow) madrasa policy in the integration of the National Education System and the low level of public appreciation in efforts to develop madrasas. Even so, madrasas must try as optimally as possible to deal with problems in the future to carry out reforms in the madrasa system. This study aims to find out the renewal of madrasah education in Indonesia and find out about the renewal of madrasah education in Indonesia according to Prof. Dr. H. Abuddin Nata, MA The type of this research is library research, using an approach method, which means that the materials and data used in the research were obtained from books and other sources related to this research. The conclusion of this research is that the renewal of madrasah education in Indonesia, according to Prof. Dr. H. Abuddin Nata, MA Namely evaluation is important in carrying out updates, and implementing patterns of maintaining old traditions that are still good, as well as taking new traditions that are even better, the development and progress of science and technology are used proportionally in managing curriculum and learning methods so as to achieve insight values in global competition and a modern education management system.